2014
DOI: 10.1152/ajpregu.00061.2014
|View full text |Cite
|
Sign up to set email alerts
|

Female sex hormones protect against salt-sensitive hypertension but not essential hypertension

Abstract: Brinson KN, Rafikova O, Sullivan JC. Female sex hormones protect against salt-sensitive hypertension but not essential hypertension. Am J Physiol Regul Integr Comp Physiol 307: R149 -R157, 2014. First published May 14, 2014 doi:10.1152/ajpregu.00061.2014.-Initial studies found that female Dahl salt-sensitive (DS) rats exhibit greater blood pressure (BP) salt sensitivity than female spontaneously hypertensive rats (SHR). On the basis of the central role played by NO in sodium excretion and BP control, we furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…Indeed, female SHRs have much greater NOS expression than Dahl salt‐sensitive rats; as a result, it is not surprising that the effect of OVX is more pronounced in SHRs. 50 Regardless, our results indicate that timing may be a critical determinant of post‐OVX outcomes on the renal NOS system. The decrease in NOS activity with OVX was likely independent of BP given that we and others have reported that OVX does not alter BP in female SHRs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, female SHRs have much greater NOS expression than Dahl salt‐sensitive rats; as a result, it is not surprising that the effect of OVX is more pronounced in SHRs. 50 Regardless, our results indicate that timing may be a critical determinant of post‐OVX outcomes on the renal NOS system. The decrease in NOS activity with OVX was likely independent of BP given that we and others have reported that OVX does not alter BP in female SHRs.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, OVX of Sprague‐Dawley rats at 4 weeks, 8 Dahl salt‐sensitive rats (on 0.1% NaCl) at 3 months 17 or Fischer‐344 rats at 3 to 4 months 31 does not alter cortical or medullary total NOS expression when studied 6 weeks to 6 months post‐OVX. Based on the dependence on the NOS system to limit increases in BP in female SHRs, 37,50 we speculate that they have a greater sensitivity to estrogen‐mediated loss of NOS. Indeed, female SHRs have much greater NOS expression than Dahl salt‐sensitive rats; as a result, it is not surprising that the effect of OVX is more pronounced in SHRs.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it is well established that the AT 2 R exerts its actions through a pathway mediated by nitric oxide (NO) (7). Given that NO opposes the renal actions of ANG II, it is plausible that greater activation of the renal AT 2 R in adult females contributes to the functional role of NO in female kidneys as well as slowing the progression of age-dependent NO deficiency and renal dysfunction (3,4). Consistent with this hypothesis, the salt sensitivity of arterial pressure increased with age in male, but not female, mice.…”
Section: Discussionmentioning
confidence: 99%
“…100 In addition, OVX female DSS rats fed a high salt diet developed hypertension in a manner that was not significantly different from males. 107 However, when dietary sodium was decreased to normal levels, blood pressure in the male and intact female DSS decreased, whereas in the OVX female DSS animals, it remained unchanged, suggesting that removing the female sex hormones predisposes the DSS female rats to develop hypertension, independent of sodium intake.…”
Section: Animal Models Of Cardiovascular Diseasementioning
confidence: 95%
“…However, supplementing OVX females with testosterone increased blood pressure by 10 percent, suggesting that androgens may mediate the observed sex difference between SHRs, 96 and that female sex hormones are not protective for hypertension in the female SHR. 100, 101 Interestingly, sex differences are also influenced by the RAS. When male and female SHR, both intact and gonadectomized, were treated with an angiotensin converting enzyme (ACE) inhibitor, sex differences were abrogated as reduced blood pressure was most significant in males and OVX females supplemented with testosterone after treatment.…”
Section: Animal Models Of Cardiovascular Diseasementioning
confidence: 99%